Pesan Kampanye Dan Efektivitas Retorika Politik - Yanto, Yanto (UNIVED PRESS, Universitas Dehasen Bengkulu, 2025)
This study aims to analyze campaign message strategies and the effectiveness of political rhetoric employed by incumbent legislative candidates from the Golkar Party in Mukomuko Regency during the 2014 Legislative Election. A qualitative approach with a case study design was applied, utilizing in-depth interviews, field observation, and campaign material documentation. The findings reveal that candidates structured their campaign messages contextually, emphasizing personal credibility (ethos), emotional closeness (pathos), and programmatic argumentation (logos). Message delivery was conducted interpersonally through social gatherings and informal meetings, reflecting the local community’s communication culture. Candidates consciously avoided negative campaigning and prioritized narratives of achievement and performance records. These findings suggest that effective political communication in local contexts requires a combination of message substance and sensitivity to prevailing social norms.